2017
DOI: 10.5004/dwt.2017.21361
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of magnetic CaFe2O4 nanoparticles for efficient adsorption of toxic Congo Red dye from aqueous solution: predictive modeling by artificial neural network

Abstract: a b s t r ac tIn this study, the performance and effectiveness of magnetic CaFe 2 O 4 nanoparticles prepared by simple chemical route were evaluated for the adsorption of toxic azo dye Congo Red (CR) from aqua matrix. The prepared CaFe 2 O 4 nanoparticles were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, vibrating sample magnetometer, point of zero charge, and Brunauer-Emmett-Teller surface area measurements. Batch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The absorption peaks from 716 to 1068 cm -1 are assigned to the vibration of NO3 -group [27]. The observed peak at 1436 cm -1 could be attributed to C-H bending vibration [35]. In addition, the broad absorption band at 3433 cm -1 could be assigned to stretching vibration of O-H [27].…”
Section: Characterization Of Cofe19zn01o4 Adsorbentmentioning
confidence: 95%
See 1 more Smart Citation
“…The absorption peaks from 716 to 1068 cm -1 are assigned to the vibration of NO3 -group [27]. The observed peak at 1436 cm -1 could be attributed to C-H bending vibration [35]. In addition, the broad absorption band at 3433 cm -1 could be assigned to stretching vibration of O-H [27].…”
Section: Characterization Of Cofe19zn01o4 Adsorbentmentioning
confidence: 95%
“…At the present study, three different solution temperatures (25,35 and 45 °C) were selected to investigate their effect on the adsorption behaviour of MB onto CFZ NPs. Besides, the other adsorption experimental conditions were fixed at the optimized values (pH value of 7, initial MB concentrations of 10 mg/L, adsorbent dosage of 0.01 g/20 mL and contact time of 90 min).…”
Section: Effect Of Solution Temperaturementioning
confidence: 99%
“…Therefore, it can be concluded that the reported methodology for sono-assisted adsorption of MR and CR dyes by MnF-PANI-NC is a superior method compared to many other reported methods on account of neutral solution pH conditions, quick attainment of equilibrium, and higher or comparable adsorption capacity of MnF-PANI-NC. [5,31,[37][38][39][40][41][42] 3.8 | Regeneration study of MnF-PANI-NC…”
Section: Isothermmentioning
confidence: 99%
“…In contrast to the %R of MB, the qe value increased significantly from 4.89 to 19.12 mg/g as the initial dye concentration was increased from 50 to 250 mg/L, as shown in Figure 6. This can be explained by the fact that, at a fixed adsorbent dose, the high initial concentration of the dye will provide the required driving to transfer the MB molecules from the bulk liquid phase to the surface of solid adsorbent [8,41,42]. In addition, the increase in the value of Figure 5.…”
Section: D) Effect Of the Initial Dye Concentrationmentioning
confidence: 99%